2015
DOI: 10.1038/jcbfm.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Fracture Exacerbates Traumatic Brain Injury Outcomes and Neuroinflammation in a Novel Mouse Model of Multitrauma

Abstract: Multitrauma is a common medical problem worldwide, and often involves concurrent traumatic brain injury (TBI) and bone fracture. Despite the high incidence of combined TBI and fracture, preclinical TBI research commonly employs independent injury models that fail to incorporate the pathophysiologic interactions occurring in multitrauma. Here, we developed a novel mouse model of multitrauma, and investigated whether bone fracture worsened TBI outcomes. Male mice were assigned into four groups: sham-TBI +sham-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 41 publications
(81 reference statements)
8
42
2
1
Order By: Relevance
“…The expression of claudin-5 significantly decreased in a pMCAO rodent model [45, 46], which was responsible for increased BBB permeability and secondary brain edema. Recent studies have shown that tibia fracture exacerbates traumatic brain BBB disruption and edema [32, 33]. However, our study showed that tibia fracture post-stroke did not reduce claudin-5 expression further when compared with stroke-only mice.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The expression of claudin-5 significantly decreased in a pMCAO rodent model [45, 46], which was responsible for increased BBB permeability and secondary brain edema. Recent studies have shown that tibia fracture exacerbates traumatic brain BBB disruption and edema [32, 33]. However, our study showed that tibia fracture post-stroke did not reduce claudin-5 expression further when compared with stroke-only mice.…”
Section: Discussioncontrasting
confidence: 80%
“…We showed in this study that tibia fracture after ischemic stroke increases brain edema, which has been observed to occur as early as three hours after MCA occlusion in a rat MCAO model, reaching the maximum level on the third day and then gradually diminishing thereafter [31]. Bone fracture has also been shown to exacerbate brain edema and worsen the outcomes of traumatic brain injury in a multitrauma mouse model [32, 33]. Brain edema plays a critical role in neuronal damage, and clinical deterioration is often associated with brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TBI, whether associated with a fall, motor vehicle accident, sports injury, or assault, often occurs concomitantly with other injuries. While studies have begun to investigate combined injuries such as TBI and bone fractures 8789 , future opportunities exist to expand this research and study combined injuries that often occur in the clinical setting, such as TBI with hypoxia, and TBI with hypoglycemia. Furthermore, future opportunities exist to expand the mFPI model to repetitive head injury studies.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described (Shultz et al, 2014b(Shultz et al, , 2015b(Shultz et al, , 2015c, MRI scanning was performed after the completion of behavioral testing (n ¼ 6e8 rats/group) using a 4.7 T Bruker Avance III scanner with 30 cm horizontal bore and fitted with a BGA12S2 actively shielded gradient set capable of 440 mT/m and actively decoupled volume transmit and 4-chanel surface receive coils. Anaesthetized animals were positioned supinely on an animal cradle with stereotactic fixation and a nose cone positioned over the rat's snout to maintain anesthesia.…”
Section: Mri Acquisitionmentioning
confidence: 99%
“…All volumetric analysis procedures followed those previously described (Johnstone et al, 2015;Shultz et al, 2015bShultz et al, , 2015cShultz et al, , 2014aShultz et al, , 2014b. Volumes of eight manually drawn regions of interest (ROI), including the cortex, hippocampus, corpus callosum, and lateral ventricles from both hemispheres, were quantified using the T 2 -weighted MRI images (FSL, Analysis Group, Oxford, UK).…”
Section: Mri Analysismentioning
confidence: 99%